2010
DOI: 10.1103/physrevlett.105.057003
|View full text |Cite
|
Sign up to set email alerts
|

Two-Orbital Model Explains the Higher Transition Temperature of the Single-Layer Hg-Cuprate Superconductor Compared to That of the La-Cuprate Superconductor

Abstract: In order to explore the reason why the single-layered cuprates, La(2-x)(Sr/Ba)(x)CuO4 (T(c)≃40  K) and HgBa2CuO(4+δ) (T(c)≃90  K) have such a significant difference in T(c), we study a two-orbital model that incorporates the d(z2) orbital on top of the d(x2-y2) orbital. It is found, with the fluctuation exchange approximation, that the d(z2) orbital contribution to the Fermi surface, which is stronger in the La system, works against d-wave superconductivity, thereby dominating over the effect of the Fermi surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
214
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(243 citation statements)
references
References 26 publications
24
214
4
1
Order By: Relevance
“…Exact numerical determination of E z 2 is still a matter of debate [14,33]. For a tetragonal system, E z 2 generally depends on the ratio between copper to apical and planar oxygen distances [34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Exact numerical determination of E z 2 is still a matter of debate [14,33]. For a tetragonal system, E z 2 generally depends on the ratio between copper to apical and planar oxygen distances [34].…”
Section: Discussionmentioning
confidence: 99%
“…3) motivates a two-band model. It has been demonstrated that d z 2 states contribute to effectively increase the t hopping parameter [14]. Keeping Z = 1.219 as in La 2 CuO 4 [8] and t = −t /2, a satisfactory description (solid line in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations